Integration of Cultural Literacy in Elementary School Curriculum: n Empirical and Conceptual Literature Analysis - Farida Kusumawati; Linda Zakiah; Mahmud Yunus (LPPM STKIP Kusuma Negara, 2026)
This study explores the integration of cultural literacy within the elementary school curriculum through an analysis of empirical and conceptual literature published between 2020 and 2025. Using a Systematic Literature Review (SLR) approach guided by PRISMA 2020, nine primary studies were analyzed to identify patterns, challenges, and opportunities in implementing cultural literacy in basic education. The reviewed studies most prominently addressed local cultural knowledge, cultural identity, and intercultural communication, with digital storybooks, VR/AR-based learning, and project-based field experiences emerging as the most effective strategies for enhancing students’ cultural understanding, engagement, and reading literacy. In contrast, limitations such as unequal technological access, varying levels of teacher competence, and inconsistent availability of culturally relevant learning materials were identified as key barriers. Conceptually, cultural literacy was consistently framed through cognitive, affective, and social dimensions aligned with the Pancasila Student Profile. The study concludes that integrating cultural literacy into the curriculum offers strong pedagogical value and recommends strengthening teacher capacity, expanding digital and print cultural resources, and conducting cross-regional research to build more generalizable evidence for policy development.